Ishwar S. answered • 09/08/18

Tutor

5
(7)
University Professor - General and Organic Chemistry

Hello Emilee

Let f = the 1st #, s = the 2nd # and t = the 3rd #.

Eq 1) f = 2s

Eq 2) t = 2f

Eq 3) f + s + t = 126

Rearrange Eq 1) to solve for s gives s = f/2. Now substitute this value of s, and Eq 2) into Eq 3), you get

f + f/2 + 2f = 126

Multiply both sides by 2

2f + f + 4f = 252

7f = 252

f = 252/7 = 36

s = f/2 = 36/2 = 18

t = 2f = 2 x 36 = 72

To confirm, f + s + t = 36 + 18 + 72 = 126!